1992
DOI: 10.1002/app.1992.070441012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of curing accelerators on physical properties of epoxy molding compound (EMC)

Abstract: SYNOPSISThe effects of various curing accelerators on the physical properties of epoxy molding compounds (EMCs) were investigated. Such properties as elasticities in rubbery and glassy regions, glass transition temperature, thermal expansion coefficient, and water absorption at 60°C of neat epoxy resins using various curing accelerators were found to be directly reflected in the properties of the EMCs that were prepared by using each resin system. However, volume resistivity and saturated water absorption at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Results of epoxy resins cured by PH-C and Ph-D show the same trend. This confirms the relationship between crosslinking density and physical properties observed by Ogata et al from epoxy molding compound [9]. They showed that the crosslinking density is related to the free volume in the cured epoxy resins and is the most dominant factor that determines various physical properties of the resins.…”
Section: Thermo-mechanical Properties Of Cured Underfillssupporting
confidence: 79%
“…Results of epoxy resins cured by PH-C and Ph-D show the same trend. This confirms the relationship between crosslinking density and physical properties observed by Ogata et al from epoxy molding compound [9]. They showed that the crosslinking density is related to the free volume in the cured epoxy resins and is the most dominant factor that determines various physical properties of the resins.…”
Section: Thermo-mechanical Properties Of Cured Underfillssupporting
confidence: 79%
“…It is considered that enough space is needed for the small segment of polymer chains to become movable at the glass transition temperature and the expansion of space becomes 1. 4 times that of volume at room temperature for these epoxy compounds. Epoxy compounds consisting of THPM have a low moisture resistance compared with other novolac epoxy compounds and this is consistent with the fact that the hole volume determined by 73 is larger than those of the others.…”
Section: Resultsmentioning
confidence: 98%
“…To improve the solder joint reliability, underfill is used between the chip and the substrate. The properties of underfill materials, such as curing behavior, CTE, Tg, storage modulus (G) and viscosity (η), are of great interest since they are crucial to the package reliability [1]. Typical commercially available underfill materials consist of an epoxy system that includes curing agent, catalysts, fillers such as SiO 2 , and additives.…”
Section: Introductionmentioning
confidence: 99%